If f(x) = 2x^2 - 3x + 2, what is f(-2/3)?

2 Answers
Mar 20, 2018

44/9 or 4 8/9 or 4.88889 Because f(x)=2x^2-3x+2, and f(-2/3), this means -2/3 should be inserted for x.

Explanation:

(-2/3)^2=(-2/3)*(-2/3)=4/9
4/9*2=8/9
-3*(-2/3)=(-2*-3)/3=6/3=2
2+2+8/9=4 8/9= 4.88889

Mar 20, 2018

f(-2/3)=44/9

Explanation:

Simply plug in -2/3 for x into f(x):

color(white)=f(-2/3)

=2(-2/3)^2-3(-2/3)+2

=2((-2)^2/3^2)-3(-2/3)+2

=2(4/9)-3(-2/3)+2

=(2*4)/9-3(-2/3)+2

=8/9-3(-2/3)+2

=8/9+3(2/3)+2

=8/9+color(red)cancelcolor(black)3(2/color(red)cancelcolor(black)3)+2

=8/9+2+2

=8/9+4

=8/9+36/9

=8/9+36/9

=(8+36)/9

=44/9~~4.888889

We can use a calculator to check our work:

https://www.desmos.com/calculatorhttps://www.desmos.com/calculator